1998
DOI: 10.1128/jcm.36.1.94-99.1998
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Performance and Cost-Effectiveness of Direct Fluorescent-Antibody, Ligase Chain Reaction, and PCR Assays for Verification of Chlamydial Enzyme Immunoassay Results for Populations with a Low to Moderate Prevalence of Chlamydia trachomatis Infection

Abstract: Many laboratories use a commercial enzyme immunoassay (EIA) with verification testing to diagnose Chlamydia trachomatisinfections in an effort to contain costs. This study was designed to compare the performance and cost-effectiveness of direct fluorescent-antibody assay (DFA), commercial PCR, and ligase chain reaction (LCR) for the verification of EIA results. Cervical specimens were screened by EIA. DFA, PCR, and LCR were compared as verification tests for EIA-reactive specimens and negative greyzone (NGZ) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…However, this lower prevalence in the latter study may reflect the fact that only urine was used for screening. Previous research has shown that urine testing will miss up to 30% of endocervical C. trachomatis infections [19,29]. Interestingly, in the only published study from the PICT of non-pregnant females, urine testing showed a prevalence of 36% among women 18 to 29 years of age in Samoa [30], suggesting that genital prevalence may be even higher.…”
Section: Discussionmentioning
confidence: 98%
“…However, this lower prevalence in the latter study may reflect the fact that only urine was used for screening. Previous research has shown that urine testing will miss up to 30% of endocervical C. trachomatis infections [19,29]. Interestingly, in the only published study from the PICT of non-pregnant females, urine testing showed a prevalence of 36% among women 18 to 29 years of age in Samoa [30], suggesting that genital prevalence may be even higher.…”
Section: Discussionmentioning
confidence: 98%
“…Although many studies have established optimal strategies for testing at-risk women, few studies have focused on women with a low prevalence of infection (18)(19)(20)(21). Howell et al (22) evaluated screening strategies for genital CT infection in Figure 3) Clinical reasons for physicians' assessment of women asymptomatic women attending two family practice clinics (6.6% overall prevalence of CT infection).…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have established optimal strategies for testing at-risk women, few studies have focused on women with a low prevalence of infection (18)(19)(20)(21). Howell et al (22) evaluated screening strategies for genital CT infection in asymptomatic women attending two family practice clinics (6.6% overall prevalence of CT infection).…”
Section: Discussionmentioning
confidence: 99%